Comparison of the Utilization of Fly Ash with Calcium Carbonate as Supplementary Cementitious Materials: Perbandingan Penggunaan Fly Ash Dengan Kalsium Karbonat Sebagai Bahan Tambah Semen - Bing Santosa; Arusmalem Ginting; Imam Syarif Hidayatulloh; Resqi Prananda (PUBLIKASI RISET ORIENTASI TEKNIK SIPIL (PROTEKSI), 2025)
Commonly used supplementary cementitious materials include fly ash and calcium carbonate. Based on this, necessary to study the comparison of the use fly ash with calcium carbonate as supplementary cementitious materials. The addition of cement with fly ash and calcium carbonate is 5%, 10%, 15% and 20% of the weight of the cement. Each variation consists of 2 concrete cylinder specimens, and a total of 18 specimens. The tests carried out were slump value and compressive strength tests. The results of the study showed that the fly ash used is classified as class C pozzolan, while calcium carbonate is not included in pozzolan. The addition of cement with fly ash and also calcium carbonate 5% to 20% increases the slump value. The addition of cement with fly ash produces a lower slump value than the addition of 10% to 20% calcium carbonate, and higher at 5%. The compressive strength of concrete with the addition of cement with fly ash is higher and calcium carbonate is lower compared to normal concrete up to an addition of 20%.. The compressive strength of concrete with the addition of cement with fly ash is higher than the addition of calcium carbonate up to 20%.